Gut, oral, and nasopharyngeal microbiota dynamics in the clinical course of hospitalized infants with respiratory syncytial virus bronchiolitis - Roggiani, Sara; Zama, Daniele; D’Amico, Federica; Rocca, Alessandro; Fabbrini, Marco; Totaro, Camilla; Pierantoni, Luca; Brigidi, Patrizia; Turroni, Silvia; Lanari, Marcello (Frontiers in Cellular and Infection Microbiology, 2023)
Respiratory syncytial virus (RSV) is the most common cause of bronchiolitis and hospitalization in infants worldwide. The nasopharyngeal microbiota has been suggested to play a role in influencing the clinical course of RSV bronchiolitis, and some evidence has been provided regarding oral and gut microbiota. However, most studies have focused on a single timepoint, and none has investigated all three ecosystems at once. Here, we simultaneously reconstructed the gut, oral and nasopharyngeal microbiota dynamics of 19 infants with RSV bronchiolitis in relation to the duration of hospitalization (more or less than 5 days). Fecal samples, oral swabs, and nasopharyngeal aspirates were collected at three timepoints (emergency room admission, discharge and six-month follow-up) and profiled by 16S rRNA amplicon sequencing. Interestingly, all ecosystems underwent rearrangements over time but with distinct configurations depending on the clinical course of bronchiolitis. In particular, infants hospitalized for longer showed early and persistent signatures of unhealthy microbiota in all ecosystems, i.e., an increased representation of pathobionts and a depletion of typical agepredicted commensals. Monitoring infant microbiota during RSV bronchiolitis and promptly reversing any dysbiotic features could be important for prognosis and long-term health.